ENERGY EFFICIENT DESIGN OF AUTONOMOUS VEHICLE BASED STORAGE AND RETRIEVAL SYSTEM - Akpunar, Anıl; Ekren, Banu Yetkin; Lerher, Tone (Journal of Applied Engineering Science, 2017)
Autonomous warehousing is moving beyond traditional crane-based AS/RS technologies on the way to autonomous vehicle (AV) based AS/RS (AVS/RS) technologies. AVS/RS proposes substantial flexibility with respect to throughput capacity in the transfer of unit loads in high density storage areas due to having opportunity in changing the number of AVs in the system. Because of recent trend in ecological concern, an efficient AVS/RS warehouse design should not only consider minimization of cycle time of a transaction to process but also consider the minimization of energy consumption in the system. In this study, we explore energy minimum AVS/RS warehouse design providing maximum utilization of resources in the system. We consider, rack design in terms of number of aisles, tiers and bays as well as number of AVs as decision variables in the design and, energy minimization as objective function. We completed 81 simulation experiments for different levels of those decision variables and provide the results via a histogram graph.